PERBANDINGAN KEGAGALAN PENYAPIHAN VENTILASI MEKANIK ANTARA T-PIECE DAN CPAP - , dr. Ayu Rosema Sari ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: Weaning from mechanical ventilation procedure is often done in the ICU. There are several ways that can be used for the weaning process, including the T-piece and CPAP. The purpose of this study was to compare the mechanical ventilation weaning failure between T-piece and CPAP. Methods: This study was an open randomized controlled clinical trials. Subjects were adult patients in ICU Dr Sardjito Hospital, planned to be weaned and meet the criteria for weaning from mechanical ventilation. All patients or family signed informed consent. Exclusion criteria were refusal to participate and patients with tracheostomy. Drop out criteria were unable to apply research procedure, withdrawal of consent after randomization and autoextubation. Sampling conducted in consecutive sampling and block randomly. The patients were divided into two groups, group T (T-piece with O2 supply 4L/minutes) and group C (CPAP with PEEP 5cmH2O and FiO2 â¤ 0,4), evaluated for 2 hours to determine whether the patient feasible for extubation. When the patient was considered feasible for extubation, the extubation was performed. Otherwise patients returned to the previous mode and re-evaluated. Mechanical ventilation weaning was determined to be successfull when the patient did not reintubated within the first 24 hours after extubation. If the patient showed any signs of respiratory failure within 24 hours, then the patient was intubated and connected to a ventilator. Results: There were very significant differences (p <0.01) for weaning failure in patients with T-piece. Weaning failure observed in patients with T-piece was 33,3% while for CPAP 0% (p = 0.007). Conclusion: CPAP had lower weaning failure than T-piece (0% vs 33,3%